CASE REPORT OF SEVERE CYTOMEGALOVIRUS INFECTION IN PREGNANCY: PREVENTION AND TREATMENT OPTIONS - Uljarevic, Jelica; Stankovic, Marko; Drobnjak, Suzana; Tosovic, Gordana; Karadzov Orlic, Natasa (Medical Research, 2025)
Introduction: Human cytomegalovirus (CMV) is the leading cause of congenital infection worldwide. It can be the cause of serious clinical manifestations, leading to permanent disability in infected children. Unlike most other TORCH infections, both primary and non-primary CMV infection can affect fetus.Patient Review: We present a case of congenital CMV infection that was diagnosed after the onset of severe fetal anomalies in the third trimester. The patient was referred to our hospital in 35. weeks of pregnancy complicated by severe intrauterine growth restriction and fetal brain anomalies seen on the ultrasound and magnetic resonance imaging (MRI): simplified gyration and a highly suspected band heterotopia (differential diagnosis: lissencephaly), dilated temporal and occipital horns of lateral ventricles with intraventricular septations, vermian hypoplasia, zones of t2 hyperintense lesions. Serology testing revealed positive results for CMV-specific IgM antibodies and a positive result for CMV-specific IgG antibodies with high avidity (91,7%). After performing the amniocentesis (PCR), we got positive result for CMV. The patient was informed about the poor prognosis of the congenital CMV infection with those findings on the fetal brain. She opted for the termination of pregnancy.Conclusion: Given that this is the most common congenital infection, it is necessary to continually raise awareness among pregnant women about primary prevention methods. In the meantime, efforts should focus on research aimed at timely detection and treatment, to prevent severe forms of congenital infection.
Keywords: kongenitalna infekcija, citomegalovirus, skrining, antivirusna terapija